2001
DOI: 10.1128/jb.183.18.5385-5394.2001
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by the Fungal Pathogen Candida albicans : Development, Architecture, and Drug Resistance

Abstract: Biofilms are a protected niche for microorganisms, where they are safe from antibiotic treatment and can create a source of persistent infection. Using two clinically relevant Candida albicans biofilm models formed on bioprosthetic materials, we demonstrated that biofilm formation proceeds through three distinct developmental phases. These growth phases transform adherent blastospores to well-defined cellular communities encased in a polysaccharide matrix. Fluorescence and confocal scanning laser microscopy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
1,402
5
41

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,430 publications
(1,502 citation statements)
references
References 51 publications
54
1,402
5
41
Order By: Relevance
“…Colorimetric assays are valuable for quantifying the viabilities of eukaryotic cells, and it has been suggested the XTT assay is useful to study fungal biofilm formation and drug resistance (Chandra et al ., 2001; Kuhn et al ., 2002). Findings from our XTT assay showed that metabolic activity of biofilm and planktonic C. albicans cells was not affected after 7‐benzyloxyindole treatment at 0.02 and 0.05 mM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Colorimetric assays are valuable for quantifying the viabilities of eukaryotic cells, and it has been suggested the XTT assay is useful to study fungal biofilm formation and drug resistance (Chandra et al ., 2001; Kuhn et al ., 2002). Findings from our XTT assay showed that metabolic activity of biofilm and planktonic C. albicans cells was not affected after 7‐benzyloxyindole treatment at 0.02 and 0.05 mM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Much like bacterial infections, fungi that cause musculoskeletal infections form biofilms [1]. Fungi in biofilms are resistant to antifungals, requiring 100 to 10009 minimum inhibitory concentration [3].…”
Section: Introductionmentioning
confidence: 99%
“…Bien d'autres définitions ont été proposées mais les fondements restent les mêmes, à savoir une structure complexe de cellules incluses dans une matrice extracellulaire (MEC) [37] (➜). Parmi les différentes espèces de Candida impliquées dans la formation de biofilms, C. albicans est l'espèce qui a fait l'objet des études les plus nombreuses [8,9]. Elle est également l'espèce la plus fréquemment impliquée en cas de candidémie avec une fréquence qui varie, selon les régions géographiques, de 37 % en Amérique latine à 70 % en Norvège [1,10].…”
Section: Les Biofilms De Candidaunclassified
“…Cet attachement initial est très rapidement suivi du développement fongique [13]. Chandra et al [9] ont décrit le déroulement de la formation du biofilm de C. albicans en distinguant trois phases : la phase précoce, la phase intermédiaire et la phase de maturation. La phase précoce concerne les onze premières heures du dévelop-pement.…”
Section: Verrous Fongiques : Modèles Et Efficacitéunclassified